HUTAN : SATU TEMPAT, BERAGAM SUDUT PANDANG - Tupan, Joberth (Universitas Kristen Satya Wacana, 2016)
Industrial approach by parties outside the community is often a problem for people in the community who still up hold the values of regionalism. Decentralization deemed incapable to answer needs of the community, and even alienating society. Local governments often decentralized approach to promote industrial development vision and mission of each region. It then presents the resistance of society as happened in the village Hatunuru. Hatunuru public notice that the palm oil industries which are negotiatedby the Regents of Western Seramand investors will have an impacton the degradation values of ecological, social, culturaland economic, and a landing people in poverty. With the help of formal and informal organizations, communities and then find the true meaning of development, and wants development without losing sight of the forest as the utility sentrum community life. Therefore, the idea of bottom-up development should be considered in order to develop rural Hatunuruas rural in the stage of development of post-resistance.